الجزية في الدول الإسلامية اليوم: رؤى معاصرة (Jizya in the the Muslim World Today: A Contemporary View) - Mohammad Hammad, Hamza Abed al-Karim (Journal of Al-Tamaddun, 2011)
This study aims to answer the main research question: What is the contemporary Fuqaha viewpoint of Imposing the Jizya on non-Muslims in modern Muslim states? The study uses an analytical, deductive reasoning approach. Viewpoints of some contemporaries in this issue were gathered, investigated and analyzed. The study concluded that most contemporary researchers see that ’Jizya’ should not be imposed on non-Muslims nowadays for the reason that jizya is a substitute for military service and defending Muslim states. Additionally, the imposition of jizya is touching upon human rights issue that most countries in the world respect. Furthermore, jizya imposition has a negative impact on relations between Muslim states and other countries.This study recommends more research on problematic issues in Islamic history is to be conducted. For instance, in contemporary world order - What is the Islamic viewpoint of imposing taxes on non-Muslims citizens so as to be treated as equal to Muslims who pay them? Moreover, it recommends to investigate Islamic fiqh (Islamic, religious jurisprudence) viewpoint on issues that have become internationally a mass public opinion especially if they are inconsistent with Islamic principles - whether Islamic fiqh accepts these issues due to necessity or reject them, if there are evidences and proofs that Islam is to take into consideration public opinions and to what extent public opinion can influence shar?a (Islamic religious) rules.